Potential inhibitor of breast cancer major protease (HER2+) using compounds from Allium sativum and Curcuma longa (Research, Society and Development, 2022)
This research aims to determine the inhibitory potential of Curcuma longa and Allium sativum in breast cancer protein (HER2+). This is an exploratory descriptive research with qualitative and quantitative characteristics. As a data collection instrument, the Inverse Virtual Screening was used in order to identify the therapeutic targets for the substances identified in the two analyzed plants (Allium sativum L. and Curcuma longa). The analysis of the results showed that the components that obtained the Tanimoto coefficient of 1 were curcumin and quercetin, which characterize ideas for the protease in breast cancer. On the other hand, the compounds present in garlic had a Tanimoto coefficient lower than 1, which indicates that they are not ideal/specific for the cancer protease under study. We concluded that when comparing the inhibitory potential of Curcuma longa (turmeric) and Allium sativum (garlic) for breast cancer protease (HER2+), Curcuma longa was the most effective, through its flavonoids curcumin and quercetin, whose coefficient of tanimoto were 1, characterizing them ideal for the breast cancer protease under study.